DISINVASIVE EFFICACY OF MODERN DISINFECTANTS ON INVASIVE LARVES OF TRICHOSTRONGYLUS TENUIS NEMATODES - Yevstafieva, V.; Starodub, Ye.; Melnychuk, V. (Scientific Progress & Innovations, 2022)
Parasitic diseases of waterfowl account for a significant share of other diseases and cause significant damage to cattle breeding. Infections caused by nematodes parasitizing in the gastrointestinal tract of birds, including trichostrongylosis, are quite common among goose helminthiases. Therapeutic and preventive measures should be performed taking into account the peculiarities of the life cycle of helminths and be aimed at the effective destruction of pathogens at different stages of their development. The aim of the research was to establish the disinvasive activity of modern disinfectants against invasive larvae of trichostrongyluses nematodes parasitizing domestic geese. Determination of disinvasive activity of disinfectants of domestic production Virosan (LTD «BioTestLab»), Dezsan (LTD «BROVAPHARMA») and Hermetsyd-VS (LTD «Vetsyntez») was determined. Invasive larvae of trichostrongyluses have been found to be more resistant to disinfectants than nematode eggs. In particular, a high level of disinvasive efficiency of Dezsan was established: in relation to T. tenuis eggs – in 1–2 % concentrations at exposures of 10–60 min (DE – 94.87–100 %); relative to invasive larvae of T. tenuis – at 2% concentration at exposures of 30–60 min (DE – 92–100 %). Virosan showed a high level of disinvasive efficiency against T. tenuis eggs – in 0.25 % concentration at exposures of 60 min (DE – 91.26 %) and at 0.5 % concentration at exposures of 10–60 min (DE – 100 %). Regarding invasive T. tenuis larvae at maximum concentration (0.5 %) and exposures of 30–60 min, Virosan showed a satisfactory level of disinvasive efficiency (DE – 66.67–79.33 %). The disinfectant Hermetsyd-VS showed a high level of disinvasive efficiency: in relation to T. tenuis eggs – in 0.25 % concentration at exposures of 30–60 minutes and at 0.5 % concentration at exposures of 10–60 minutes (DE – 100 %) ; relative to invasive larvae of T. tenuis – in 0.25 % concentration at exposures of 60 min (DE – 90 %) and at 0.5 % concentration at exposures of 10–60 min (DE – 98.67–100 %). It is recommended to use 2 % Dezsan solution at exposures of 60 minutes and 0.5 % Hermetsyd-VS solution at exposures of 10–60 minutes to disinfect poultry houses and pastures for goose trichostrongylosis.